Blending Formative and Summative Assessment in a Capstone Subject: ‘It’s not your tools, it’s how you use them’ - Houston, Don; Thompson, James (Journal of University Teaching and Learning Practice, 2017)
Discussions about the relationships between formative and summative assessment have come full circle after decades of debate. For some time formative assessment with its emphasis on feedback to students was promoted as better practice than traditional summative assessment. Summative assessment practices were broadly criticised as distanced from the learning process. More recently discussions have refocused on the potential complementary characteristics of formative and summative purposes of assessment. However studies on practical designs to link formative and summative assessment in constructive ways are rare. In paramedic education, like many other professional disciplines, strong traditions of summative assessment - assessment ‘of’ learning - have long dominated. Communities require that a graduate has been judged fit to practice. The assessment redesign described and evaluated in this paper sought to rebalance assessment relationships in a capstone paramedic subject to integrate formative assessment for learning with summative assessment of learning. Assessment was repositioned as a communication process about learning. Through a variety of frequent assessment events, judgement of student performance is accompanied with rich feedback. Each assessment event provides information about learning, unique to each student’s needs. Each assessment event shaped subsequent assessment events. Student participants in the formal evaluation of the subject indicated high levels of perceived value and effectiveness on learning across each of the assessment events, with broad agreement also demonstrated relating to student perceptions for preparedness: ‘readiness to practice’. Our approach focused on linking assessment events, resulted in assessments providing formative communication to students and summative outcome information to others simultaneously. The formative-summative dichotomy disappeared: all assessment became part of communication about learning.